2017
DOI: 10.1186/s12888-016-1184-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sarcoidosis resembling panic disorder: a case report

Abstract: BackgroundSarcoidosis is a systemic disease of unknown etiology, in which granulomas develop in various organs, including the skin, lungs, eyes, or heart. It has been reported that patients with sarcoidosis are more likely to develop panic disorder than members of the general population. However, there are many unknown factors concerning the causal relationship between these conditions.Case presentationWe present the case of a 57-year-old woman who appeared to have panic disorder, as she experienced repeated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…SLE is associated with an increased risk of mental health symptoms [ 35–37 ], with estimates of ≈70% of patients having neuropsychiatric manifestations [ 36 ]. Prevalence of depression in SLE is estimated at 30–50% [ 35 , 37 ], and one study found that ≈20–50% of rheumatological patients have psychosocial problems attributable to their disease, which were frequently not discussed with their physician [ 38 ]. Failure to elicit mental health symptoms is therefore of concern, particularly give that many of our participants also felt their mental health was directly damaged by difficult diagnostic journeys and/or negative medical interactions.…”
Section: Discussionmentioning
confidence: 99%
“…SLE is associated with an increased risk of mental health symptoms [ 35–37 ], with estimates of ≈70% of patients having neuropsychiatric manifestations [ 36 ]. Prevalence of depression in SLE is estimated at 30–50% [ 35 , 37 ], and one study found that ≈20–50% of rheumatological patients have psychosocial problems attributable to their disease, which were frequently not discussed with their physician [ 38 ]. Failure to elicit mental health symptoms is therefore of concern, particularly give that many of our participants also felt their mental health was directly damaged by difficult diagnostic journeys and/or negative medical interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we report the results of a pilot study of the intervention. This was done as we are aware that large expensive RCTs with this population have failed due, in part, to not being able to recruit participants [16] or not being feasible to implement in routine clinical practice [17, 18], and it is therefore essential to identify which of these barriers may be most relevant for WTW before conducting a fully powered randomised controlled trial. Eldridge and colleagues [19] recommend carrying out randomised pilot studies where ‘ the future RCT, or parts of it, including the randomisation of participants, is conducted on a smaller scale (piloted) to see if it can be done’ (p 14/15).…”
Section: Introductionmentioning
confidence: 99%